Psychosocial Interventions for Reducing Suicidal Behaviour and Alcohol Consumption in Patients With Alcohol Problems: A Systematic Review of Randomized Controlled Trials. (17th October 2020) - Hurzeler, Tristan; Giannopoulos, Vicki; Uribe, Gabriela; Louie, Eva; Haber, Paul; Morley, Kirsten C
Abstract: Objective: We aimed to provide a synthesis and evaluation of psychosocial interventions to prevent suicide and reduce self-harm, as well as alcohol intake, for patients with alcohol problems. Methods: The systematic review was carried out according to the PRISMA guidelines and considered articles published in English from all countries. Terms relating to suicidality and alcohol problems were used to search Medline, EMBASE and PsycINFO databases. Randomized controlled trials of psychosocial interventions targeted for outpatient settings were included. Results: Six studies with a total of 400 participants were included. Two investigated dialectic behavioural therapy (DBT), one internet-delivered DBT, one dynamic deconstructivist psychotherapy (DDP) and two integrated cognitive behavioural therapy (CBT). Face to face and online DBT was significantly associated with abstinence and reductions in consumption with only a trend for a reduction in suicide attempts in one study relative to treatment at usual (TAU). DDP yielded significant reductions in alcohol consumption and suicide attempts versus community care. CBT was significantly effective relative to TAU in reducing alcohol use and suicide attempts in one trial with adolescents but not in another trial in an adult population. Conclusion: Integrated CBT has promise for adolescents, DBT may be helpful for alcohol patients with borderline personality disorder and iDBT may be useful for the wider community with heavy alcohol use. However, given the paucity of studies and the exploratory nature of these trials, there is currently no strong evidence for an effective psychosocial intervention to reduce alcohol consumption and suicidal behaviour in adults with problematic alcohol use. Abstract : Short Summary: We synthesized RCTs of psychosocial interventions to reduce suicide risk and alcohol use. Integrated CBT may have promise for adolescents while DBT may be helpful for alcohol patients with borderline personality disorder. There remains no strong evidence for an effective face to face or online psychosocial intervention in this population.